A Multi-Group Analysis of the Effect of Organizational Commitment on Higher Education Services Quality - Hamed Al-Rafaei, Abdul Al-Aziz; Zumrah, Abdul Rahim; Ali Alsamawi, Mohamed Abdulwali; Ali Alshuhumi, Said Rashid (Forecast Publisher, 2019)
Service organizations dependent on human interaction to deliver services to the customer. Hence, delivering the required level of service quality determined by employee and customer interaction through service encounter. Throughout crucial service encounter between employee and customer, it is employee’s willingness to involve in discretionary effort that influences the level of service quality that delivered to the customer (Zeithaml, Parasuraman, & Berry, 1990; Boulding, Kalra, Staelin and Zeithaml, 1993; Malhotra & Mukherjee, 2004; Chand, 2010; Tsaur and Lin, 2004; Sarkey, Turkson and Ansah, 2013; Larivière, 2017), Which mean organizations services will face more difficulties to delivering the desirable level of service quality to their customers when their frontline employees uncommitted and dissatisfied or not happy (Zeithaml, Berryand Parasuraman, 1996; Al-Refaei and Zumrah, 2019a), or unwilling to exert any additional effort to benefit there organization (Al-Refaei and Zumrah (2019b). Furthermore delivering desirable level of service quality heavily depends on the frontline employees (Al-Refaei and Zumrah (2019b), delivered service process depends on the way that employee deal with customer. However, previous studies argued that, customers' experience considered as the key issue to understanding service quality (Schneider, Parkington and Buxton, 1980; Schneider and Bowen, 1993; Parasuraman, Zeithaml, and Berry, 1988; Schneider and Bowen, 1985; Schneider, White and Paul, 1998; Gazzoli, Hancer and Kim, 2013; Jaakkola, Helkkula and Aarikka-Stenroo, 2015). Therefore, the key to managing the customer’s experience of service quality is to manage frontline employees’ experiences within their own organization, due to employ ee experiences, attitudes and behaviors is the critical link to the customer’s perception of service quality (Parkington, and Schneider, 1979; Schneider and Bowen, 1985; Gazzoli, Hancer and Kim, 2013; Oh and Kim, 2017). Furthermore, employee perceptions of organizational practices and procedures influence customer perceptions of service quality (Schneider, Parkington and Buxton, 1980). However, customers preferring to build their perception of services quality on specific employee performance rather than on global assessments of services quality (Gould-Williams and Davies, 2005). In addition researchers such as (Alshaibani and Bakir, 2017, Liao and Chuang, 2004; Liao, Toya, Lepak and Hong, 2009; Raub and Liao, 2012) argued that customer perception of service quality directly affected by service performance of front-line employees, Therefore, previous studies did not matched customers perception of service quality to perception of employee who provide service toward organizational practices and procedures, which make the relationship between organizational practices, procedures, employee attitudes and behaviour on customer perception of service quality unclear